قلق الموت عند المسنين وعلاقته بالرضا عن أهداف الحياة والنزعة الاستهلاكية - العاني، ضحى عادل محمود (جامعة بغداد - كلية التربية ابن رشد, 2015)
يتجسد قلق الموت في حالات خيبة أمل الإنسان وعجزه ومحاولاته الفاشلة في إدراك المعني لدى المسن، وإن الهدف في الحياة للمسن هو في إيجاد معني لها. لذا يسعي لذلك بالطريقة التي يسلكها، لهذا فكثير من المعاناة العصابية والكآبة تتجم عن فشل المسن في إيجاد مغزي للحياة أو إيجاد معان جديدة لها، وأن المسنين الذين يعانون من النزعة الاستهلاكية يكون سلوكهم شرها غير مسوغ نحو الاستهلاك العقلاني للسلعة والمنتجات الضرورية للعيش الرغيد؛ لأن النزعة الاستهلاكية وسيلة للتخلص من التوتر عن المسنين. وهدف البحث الحالي تعرف:- 1. مستوي قلق الموت عند المسنين. 2. مستوي الرضا عن أهداف الحياة عند المسنين. 3. مستوي النزعة الاستهلاكية عند المسنين, 4. العلاقة بين قلق الموت والرضا عن أهداف الحياة عند المسنين. 5. العلاقة بين قلق الموت والنزعة الاستهلاكية عند المسنين. 6. العلاقة بين الرضا عن أهداف الحياة والنزعة الاستهلاكية عند المسنين. 7. الكشف عن العلاقة الارتباطية بين قلق الموت والرضا عن أهداف الحياة والنزعة الاستهلاكية عند المسنين. وتضمنت عينة البحث (308) متقاعدا ومتقاعدة، ممن يستلمون رواتبهم من المصارف في مدينة بغداد تم اختيارهم عشوائيا، ومن تحليل استجابات المتقاعدين والمتقاعدات والاطلاع علي الأدبيات والدراسات السابقة، ثم التوصل إلي إعداد فقرات مقياس قلق الموت المتكون من (67) فقرة، وإعداد فقرات مقياس الرضا عن أهداف الحياة للمتقاعدين والمتقاعدات والمتكون من (66) فقرة، وإعداد فقرات مقياس النزعة الاستهلاكية للمتقاعدين والمتقاعدات المتكون من (45) فقرة. وبعد استخدام الوسائل الاحصائية اظهرت النتائج ما ياتي: ان مستوى قلق الموت كانت نسبته منخفضة عند المسنين وان مستوى الرضا عن اهداف الحياة عالية كما اظهرت النتائج ان مستوى النزعة الاستهلاكية عند المسنين متوسطة وفي تحليل البيانات لغرض امكانية التنبؤ في متغير قلق الموت من خلال المتغيرات المستقلة ( الرضا عن اهداف الحياة والنزعة الاستهلاكية) وقد تبين ان معامل الارتباط المتعدد بلغ (0.344) وهو دال عند مستوى دلالة (0.05)
Death is a natural inevitable fate and the end of every creature , death anxiety is a main source of neurotic misery and especially at the end of human life , contribute and affect the way of life because it biggest shocking factor formulates aging psychosis. And death anxiety of the elderly is materialize in human disappointment cases and inability and his unsuccessful attempts failed to grasp the meaning , and the goal in life for the elderly is to find its meaning. So it seeks for that in a way that they behave. Therefore, a lot of neuroticism suffering and depression caused by the failure of the elderly to find a meaningful life or finding new meanings to it, and that the elderly who suffer from consumerism tendency have voracious behavior and unjustified towards rational consumption for necessary goods and products to live well-off because consumerism tendency of the elderly is a way to get rid of tension. The goal of current research is to know- : 1- The level of death anxiety of the elderly. 2- The level of satisfaction with life goals in the elderly. 3- The level of consumerism tendency of the elderly. 4- The relationship between death anxiety and satisfaction with life goals of the elderly. 5- The relationship between death anxiety and consumerism tendency of the elderly. 6- The relationship between satisfaction with life goals and consumerism tendency of the elderly. 7- Detection of correlation between death anxiety and satisfaction with life goals and consumerism tendency in the elderly. Research a sample included (308) retired people , men and women ,who receive their salaries from the banks in the city of Baghdad have been selected at random , and from analysis of retirees responses, and access to theories and previous studies, , then obtaining to arrangement of items of death anxiety scale, consisting of (67) items , and arrangement of items of satisfaction with life goals scale for retirees , consisting of (66 ) items , and arrangement of items of consumerism tendency scale for retirees, consisting of (45) items.After the use of statistical methods results showed the following : The level of death anxiety rate was low of the elderly , and the level of satisfaction with life goals was high , also the results showed that the level of consumerism tendency of the elderly was average , and in the analysis of data for the purpose of predictability in the variable death anxiety through the independent variables ( satisfaction with life goals and consumerism tendency ) . It has been found that the multi correlation coefficient reached ( 0.344 ) and its function to the level of significance ( 0.05 ) , and in light of the following results some of the recommendations and the following proposals have been set .
Keywords: المسنين -- قلق الموت -- أهداف الحياة -- النزعة الاستهلاكية